Systemic factors associated with antler growth promote complete wound healing - Qianqian Guo; Guokun Zhang; Jing Ren; Jiping Li; Zhen Wang; Hengxing Ba; Zihao Ye; Ying Wang; Junjun Zheng; Chunyi Li (npj Regenerative Medicine)
Abstract Deer antlers are the only mammalian appendages that can fully regenerate from periosteum of pedicles (PP). This regeneration process starts from regenerative healing of wounds. Removal of PP abolishes antler regeneration, however, the regenerative cutaneous wound healing proceeds, indicating that some factors in the circulation contribute to this healing. In this study, we produced a wound in the scalp of deer either in antler regeneration period (ARP) (n = 3) or in non-ARP (n = 3). Results showed full regeneration took place only when the wound was created during ARP. Interestingly, topical application of systemic factors from ARP (n = 9) promoted regenerative wound healing in rats. Comparative proteomics analysis (n = 3) revealed that PRG4 and IGF-1 were high during ARP, and topical application of PRG4 + IGF-1 promoted restoration in rat FTE wounds. We believe that, ultimately, incorporating systemic factors into advanced wound care modalities could offer new opportunities for regenerative healing in the clinical setting.